From simulation to reality: experimental analysis of a quantum entanglement simulation with slime molds (Physarum polycephalum) as bioelectronic components - Schmidt, Markus; Seyfried, Günter; Reutina, Uliana; Seskir, Zeki; Miranda, Eduardo R. (Frontiers in Soft Matter, 2025)
This study investigates whether it is possible to simulate quantum entanglement with theoretical memristor models, physical memristors (from Knowm Inc.) and slime molds Physarum polycephalum as bioelectric components. While the simulation with theoretical memristor models has been demonstrated in the literature, real-world experiments with electric and bioelectric components had not been done so far. Our analysis focused on identifying hysteresis curves in the voltage-current (I-V) relationship, a characteristic signature of memristive devices. Although the physical memristor produced I-V diagrams that resembled more or less hysteresis curves, the small parasitic capacitance introduced significant problems for the planned entanglement simulation. In case of the slime molds, and unlike what was reported in the literature, the I-V diagrams did not produce a memristive behavior and thus could not be used to simulate quantum entanglement. Finally, we designed replacement circuits for the slime mold and suggested alternative uses of this bioelectric component.